Mapping the Aliran of the Academic Discipline of Entrepreneurship: A Discursive Representation - Lock, Rob (Auckland University of Technology, 2009)
In this study, I consider the status of the academic discipline of entrepreneurship as represented in refereed journal articles and citations in the Web of Science database within a broad philosophical framework, developed for this investigative purpose. This dissertation firstly explores an understanding of knowledge as offered by French social theorist, Michael Foucault, identifying two forms of knowledge. Using Foucault’s distinctions, I develop models that position savoir and connaissance knowledge, which I define as practical applications of understanding and academic orientations of explaining, in relation to disciplines and discourses. The strategic apparatus of the episteme is included in my models as a discipline-based method of determining the acceptability of knowledge into the discipline, incorporating the varied roles of gate-keepers, intellectuals and other participants into the models. The roles of epistemology and ontology are discussed and included in the models. Further, drawing on the works of German philosopher, Martin Heidegger, I introduce the concept of an ontological test as a possible means to consider whether an academic discipline clearly understands its ‘meaning of being’ or, alternatively, could be considered to have passed Foucault’s point of epistemologization and be termed a ‘dubious discipline’. Academic thinking on entrepreneurship has come under an array of criticism from within the discipline, including criticism as to a perceived lack of objectivity. The models developed in this dissertation are applied to the discipline of entrepreneurship in order to better understand the development of the discipline of entrepreneurship and the reasons for this criticism. Using the episteme of the Web of Science database, I apply citation analysis to identify those articles and texts which are considered within the entrepreneurship discipline to have the highest gravitas. These high gravitas articles are used to create an archaeological representation or aliran that illustrates the development of the discipline over time and the ontological development of sub-aliran. This aliran is a phenomenological representation of the discipline based upon the episteme to depict the episteme ‘as it is’. This representation is hermeneutically interpreted to discern the development of various sub-aliran, and identify the possible influence of gate keepers with high gravitas in such development. Based upon my survey of high gravitas articles from the aliran, I found there was a general exclusion of practitioner both as an audience for and as a source of savoir knowledge. Admittedly this finding could well be attributed to the nature of the episteme selected for the research. The exception to this general finding was in the Venture Capital sub-aliran. Further findings indicated an apparent feature of the aliran was a higher than expected level of demarcation between the organization and the firm. This demarcation had several features including an increasing trend towards learning by the organization as applied to entrepreneurship. Firms were not perceived to engage in learning but did engage in new ventures and undertook innovation. These functions were not indicated within the aliran to be part of the functions of the organization. Innovation was also not shown to be an activity conducted by individuals but was a preserve of the firm. These findings are consistent with the political structure of the Academy of Management’s Entrepreneurship Division and indicate the influence this body likely has on the discipline. In some instances, as might be expected, there was an overt level of construction of some sub-aliran by those with high gravitas in the discipline. This was most apparent in endeavours to add ‘corporate’ nominations to entrepreneurship, innovation and venturing. In the case of corporate entrepreneurship, such overt construction was perceived to be less than successful. However, the changing orientation offered by such construction is seen to offer a new direction to entrepreneurship which may be realized in the fledgling Strategic Entrepreneurship sub-aliran. Some sub-aliran observed was considered to be more introverted due to restraints imposed by the political structuring of the discipline. While the discipline of entrepreneurship may not to be able to pass Heidegger’s ontological test and could be considered a dubious discipline (doubtless like so many others), this finding should not be deemed to be unduly negative. As with Gadamer’s rehabilitation of prejudice, the term dubious could be rehabilitated to be positive and encourage moves towards greater objectivity, or at least greater rigour, within the discipline of entrepreneurship.
Keywords: Entrepreneurship; Episteme; Aliran; Practitioner; Philosophy; History of knowledge